ANALISIS METODE BIAYA PERAWATAN HAUL TRUCK DENGAN SISTEM KONTRAK PADA PT “ABC” BANJARMASIN - Teguh Suprianto; Hermansyah . (P3M Politeknik Negeri Banjarmasin, 2010)
Maintenance system contracts all this time was popular. It because of marks sense thatperception mantenance model with system contract precious been looked on by heavy equipmentowner. Therefore needs to be done by count outgrows maintenance cost with system contractswith notice reliability of heavy equipments.In this analysis will be worked through about whatever parameters that is used to determinemaintenance cost haul truck with system contracts and how methodic to account maintenancecost with system contracts that effective so can compete and advantages owner and also agentparty. In cost count contracts to be accounted by expectation point full scale downtimeequipment up to one period so gets to be determined by expectation of penalty cost. Fromexpectation Corrective Maintenance and Preventive Maintenance hereafter will bedetermined expectation of the cost contracts.